Exploration of high school students' sentiments and emotions towards mathematics: Linked to learning outcomes - Silitonga, R. H. Yanti; Dasari, Dadan; Dahlan , Jarnawi Afgani (Universitas Maritim Raja Ali Haji, 2024)
Mathematics research often focuses only on students' learning outcomes without considering their emotional aspects. This study aims to describe the tendency of students' sentiment toward mathematics in general and partially based on mathematics learning outcome groups, namely high, medium, and low. In addition, a mood analysis was conducted using Ekman's Basic Emotion classification. Data collection techniques are questionnaires and documentation. The questionnaire contains open questions about students' opinions on mathematics and closed to queries for student demographics. Documentation is done by collecting test scores from student grade books. This study used a descriptive method with data in the form of 72 comments from grade XI high school students in Bandung City, which were analyzed using the Orange Application Sentiment Analysis. The results of the study showed that (1) student sentiment was generally dominated by positive sentiment at 72.22%, (2) positive sentiment also dominated the groups of students with high, medium, and low learning outcomes, with a percentage of more than 68%, and (3) the results of the classification of emotions based on Ekman's Basic Emotion indicated that